Using Radon Transform to Recognize Skewed Images of Vehicular License Plates - Rajput H.; Som T.; Kar S. (My University, 2025)
An algorithm that projects image intensity along a radial line oriented at a specific angle enables the recognition of vehicular license plates at odd angles. The algorithm determines orientation angle, rotates the image to a horizontal perspective, and removes image noise from rotation to achieve recognition accuracy as high as 98 percent. © 2016 IEEE.